2018
DOI: 10.36834/cmej.42937
|View full text |Cite
|
Sign up to set email alerts
|

Physician perceptions of recruitment and retention factors in an area with a regional medical campus

Abstract: Background:The factors that influence physicians to establish and maintain their practice in a region are variable. The presence of a regional medical campus (RMC) could influence physicians' choice. The objective of this study was to explore the factors influencing physician recruitment and retention, and in particular the role of a RMC, in a region of Quebec. Methods:A literature review of factors influencing physicians to stay in a rural area was conducted in order to create an interview guide. Questions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Another inconsistency may also be due to the sample size of doctors in our study considering marriage. Spousal influence is considered to play a significant role in the recruitment and retention of physicians, as shown in previous studies (Cameron et al, 2012;Giberson et al, 2016;Russell et al, 2018;Levesque et al, 2018). We observed that significant differences in the anticipated retention rate were introduced because of marriage in univariate analysis, but they failed to affect the binary logistic regression model.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Another inconsistency may also be due to the sample size of doctors in our study considering marriage. Spousal influence is considered to play a significant role in the recruitment and retention of physicians, as shown in previous studies (Cameron et al, 2012;Giberson et al, 2016;Russell et al, 2018;Levesque et al, 2018). We observed that significant differences in the anticipated retention rate were introduced because of marriage in univariate analysis, but they failed to affect the binary logistic regression model.…”
Section: Discussionsupporting
confidence: 64%
“…A high turnover rate is not conducive to the formation of a stable doctor-patient relationship, which further affects the quality of medical treatment. It has been reported that various combinations of recommendations, such as the establishment of regional medical campuses (Levesque et al, 2018;William et al, 2015) and integration into the local community (Cutchin et al, 1994;Morken et al, 2018), have been implemented in many countries. The setting up of fitness equipment and entertainment facilities (Cameron et al, 2012), education of family physicians in community-based programs (Gruca & Nelson, 2017), and investment in telehealth technology have facilitated the improvement in communication in remote communities (Larsen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Factors guiding retention rates include personal, family, and professional factors [4]. Quality of life, proximity to family, and quality of work environment are positive factors that influence physician retention rates.…”
Section: Introductionmentioning
confidence: 99%